PERANAN KOPERASI SEKOLAH DALAM MENUMBUHKAN JIWA BERWIRAUSAHA PADA SISWA - Wahidin, Ohan; Widyaningsih, Dewi; Anisah, Aan; Rusdiyana, Rusdiyana; Febianti, Yopi Nisa (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
One of the objectives of establishing a School Cooperative is to foster and encourage the growth of awareness and spirit of cooperation and student entrepreneurship. School cooperatives, if run according to their functions and objectives, will clearly have an impact on the growth of students' entrepreneurial spirit, including students of SMAN Depok, Cirebon Regency. This study aims to determine the role of school cooperatives in forming an entrepreneurial spirit in students at SMA Negeri Depok, Cirebon Regency. The research method used in this study is a descriptive qualitative method. The research data sources consist of two sources, namely (1) Primary data sources, and (2) Secondary data sources. Data collection techniques in this study consist of three types, namely (1) Observation (2) Interviews, and (3) Documentation. Meanwhile, the data analysis method used in descriptive qualitative research conducted by researchers is by means of (1) Data reduction (2) Data presentation, and (3) Drawing conclusions. The results of the study obtained are that the role of school cooperative activities in forming an entrepreneurial spirit in students of SMA Negeri Depok, Cirebon Regency is good.